Amphiphilic Polymer Co‐Network: A Versatile Matrix for Tailoring the Photonic Energy Transfer in Wearable Energy Harvesting Devices. Issue 18 (19th March 2022) - Huang, Chieh‐Szu; Yakunin, Sergii; Avaro, Jonathan; Kang, Xinyue; Bodnarchuk, Maryna I.; Liebi, Marianne; Sun, Xuemei; Rossi, René M.; Kovalenko, Maksym V.; Boesel, Luciano F.
Abstract: In recent years, Förster resonance energy transfer (FRET) and related topics have received marked attention both as a subject of scientific investigation and due to its many potential applications. However, the state‐of‐the‐art matrix materials for the FRET need to be improved in terms of universal loading for all types of luminescent moieties and the matrix integrability with real‐life devices, but without sacrificing the FRET efficiency, i.e., maintaining the proximity of the embedded donors and acceptors. Amphiphilic polymer co‐networks (APCNs) are investigated as versatile matrix materials for hosting luminescent materials and realizing highly efficient FRET between hydrophobic inorganic donors (CsPbBr3 nanocrystals) and hydrophilic organic acceptors (Rhodamine B). APCNs are advantageous owing to the unique properties of their hydrophilic and hydrophobic biphasic nature and the uniformly distributed nano‐domains. The energy transfer rate can be tailored in a straightforward way by manipulating the nano‐domain sizes and volumetric distribution, so steering donor–acceptor pair loading and distances. Consequently, APCNs are used as luminescent solar concentrators for fiber solar cells, demonstrating the ability to enhance existing solar‐energy harvesting electronics via photonic energy transfer steering. APCN is demonstrated as a powerful matrix for future photonic applications in the field of energy harvesting and energy generation. Abstract : Energy transfer mechanisms, including Förster resonance energy transfer, localized‐surface plasmon resonance, and plasmon‐induced resonance energy transfer, of organic dyes, inorganic nanocrystals, and metallic nanoparticles are realized within a specially designed matrix material—amphiphilic polymer co‐networks. The energy transfer rate is successfully steered by tailoring the morphology of the matrix. The material works as a luminescent solar concentrator to boost the performance of fiber solar cells by 11%.